The Effect of Physical Activity Based on Intergenerational Programs on the Quality of Life of Older Adults - Zeenat Ebrahimi; Mohammad Reza Esmaeilzadeh Ghandehari; Kourosh Veisi (University of Social Welfare & Rehabilitation Sciences, 2020)
Objectives Quality of Life (QOL) is an important indicator in health evaluation, and its improvement reflects the preservation and enhancement of the physical and mental health of the elderly people. The purpose of this study was to examine the effect of sport intervention based on intergenerational programs on the QOL of older adults. Methods & Materials The is a quasi-experimental study with pre-test/post-test design. The samples were 150 older adults (mean age, 71.4±78.50 years) and 100 students (mean age, 21.86±2.62 years) living in Mashhad, Iran in 2017, who were selected using a convenience sampling method. They were randomly divided into three groups including two experimental groups (received two types of intergenerational programs for 8 weeks) and one control group. Data were collected using a demographic form, Socio-Economic Status Questionnaire, and the World Health Organization Quality Of  Life (WHOQOL). The collected data were analysed using two-way ANOVA in SPSS V. 25 software. Results Demographic variables had no significant effect on the QOL of participants in the study groups (P>0.05), but economic status significantly  affected their QOL (P≥0.05). The scores of QOL dimensions were significantly different in the three groups (P<0.01). Moreover, the QOL of older adults after intervention with sports activity (81.56±17.87) and without sports activity (75.18±28.59) increased significantly compared to their pre-test scores and the control group (42.28±3.21) (P<0.01). Conclusion Intergenerational programs can have a beneficial effect on the life of older adults by improving their QOL